1984
DOI: 10.1093/oxfordjournals.jbchem.a134654
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Identification of Myosin Heavy Chain Kinase from Bovine Brain

Abstract: A high salt extract of bovine brain was found to contain a protein kinase which catalyzed the phosphorylation of heavy chain of brain myosin. The protein kinase, designated as myosin heavy chain kinase, has been purified by column chromatography on phosphocellulose, Sephacryl S-300, and hydroxylapatite. During the purification, the myosin heavy chain kinase was found to co-purify with casein kinase II. Furthermore, upon polyacrylamide gel electrophoresis of the purified enzyme under non-denaturing conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…All three cell lines showed an increase in NMHC-IIB phosphorylation after EGF stimulation, yet the EGF-dependent NMHC-IIB phosphorylation in PKC␥ DN cells was 60% lower than that of control cells ( Figure 7A). These results indicate that PKC␥ is involved in EGF-dependent NMHC-IIB phosphorylation in (Murakami et al, 1984(Murakami et al, , 1998Straussman et al, 2001) may also phosphorylate NMHC-IIB. Another possibility is that the expressed PKC␥ DN did not inhibit completely the activity of the endogenous PKC␥.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…All three cell lines showed an increase in NMHC-IIB phosphorylation after EGF stimulation, yet the EGF-dependent NMHC-IIB phosphorylation in PKC␥ DN cells was 60% lower than that of control cells ( Figure 7A). These results indicate that PKC␥ is involved in EGF-dependent NMHC-IIB phosphorylation in (Murakami et al, 1984(Murakami et al, , 1998Straussman et al, 2001) may also phosphorylate NMHC-IIB. Another possibility is that the expressed PKC␥ DN did not inhibit completely the activity of the endogenous PKC␥.…”
mentioning
confidence: 75%
“…These results indicate that PKC␥ is involved in EGF-dependent NMHC-IIB phosphorylation in vivo. The incomplete inhibition of EGF-dependent NMHC-IIB phosphorylation in PKC␥ DN cells may indicate that PKC␥ is not the only kinase that phosphorylates NMHC-IIB, other kinases like CKII and members of the PKC family other than PKC␥ (Murakami et al, 1984(Murakami et al, , 1998Straussman et al, 2001) may also phosphorylate NMHC-IIB. Another possibility is that the expressed PKC␥ DN did not inhibit completely the activity of the endogenous PKC␥.…”
Section: The Effect Of Pkc␥ Overexpression On the Actomyosin Cytoskelmentioning
confidence: 99%
“…Myosin heavy-chain phosphorylation has been shown to occur in a number of nonmuscle myosins, including those from Acanthamoeba (Maruta & Korn 1977;Collins & Korn 1980Hammer et al 1983; for review, see Korn et al 1987), Dictyostelium (Kuczmarski & Spudich 1980;Kuczmarski 1986), Physarum (Ogihara et al 1983), macrophages (Trotter 1982), lymphocytes (Fechheimer & Cebra 1982), and brain cells (Matsamura et al 1982;Murakami et al 1984). For the Acanthamoeba myosin II and Dictyostelium myosin, this phosphorylation, which occurs on serine and threonine residues, inhibits both filament assembly and actin activation of myosin ATPase (Kuczmarski & Spudich 1980;Korn et al 1987;Peltz et al 1981;Pagh & Gerisch 1986).…”
Section: Cell Biology Of Myosinsmentioning
confidence: 99%
“…This enzyme phosphorylates three sites on the tail portion of the two-headed Acanthamoeba myosin (myosin II) and the effect of phosphorylation is similar to that in Dictyostelium, namely Acanthamoeba myosin phosphorylation inhibits actin-activated ATPase and selfassembly (Collins et al, 1982). Murakami et al (1984) have reported that a bovine brain kinase is capable of phosphorylating heavy and light chains of brain myosin. This enzyme did not require Ca 2+-calmodulin or cAMP for activity.…”
Section: Discussionmentioning
confidence: 99%